Effectiveness of Transparent Concrete Media for Geometry Learning in Improving Junior High School Students’ Understanding of Surface Area - Dinar Nirmalasari; Halvitri Nurul Hidayah; Claudia Salsabila (MASI Mandiri Edukasi, 2026)
Mastery of the concept of surface area in solid figures remains a challenge for junior high school students, particularly in linking three-dimensional representations with their corresponding nets. This study aimed to examine the effectiveness of transparent solid figures as concrete learning media in improving students’ understanding of surface area concepts. Conducted at SMPIT Al Mubarok, Serang City, during the 2025/2026 academic year, the study employed a quantitative method using a one-group pretest–posttest experimental design. Thirty ninth-grade students were selected through accidental sampling based on accessibility and availability. A concept comprehension test was administered before and after the treatment, and data were analyzed descriptively and inferentially. Results indicated that students’ surface-area comprehension improved significantly following the use of transparent concrete instructional media. The mean pretest score of 81.43 increased to 100 on the posttest. The Wilcoxon Signed-Rank Test revealed a significance value of 0.000 (<0.05), and the N-Gain score of 1.00 was categorized as high, confirming that transparent solid media were highly effective in enhancing students’ conceptual understanding of surface area.